The Effect of Intrinsic Motivation, Job Satisfaction, and Affec-tive Commitment on Employee Performance at the Regional Development Planning Agency - Siti Aisyatur Rohmah; Ignatius Soni Kurniawan; Tri Ratna Purnamarini (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The purpose of this study was to examine the influence of intrinsic motivation, job satisfaction, and affective commitment on employee performance at the Regional Development Planning Agency of Yogyakarta City, DI Yogyakarta. A total of 95 people provided primary data through direct surveys as part of the quantitative methodology in this study. After the regression model passed the traditional assumption test, the data were analyzed using multiple linear regression using the SPSS version 26 program. The results showed that job satisfaction had a significant positive effect on employee performance, while affective commitment and intrinsic motivation did not appear to have any effect. These results emphasize the importance of Management to focus on developing job satisfaction as a primary strategy to improve employee performance. In addition, although employee motivation and commitment are not partially significant, ensuring the quality of these elements remains important as part of a holistic approach to supporting overall organizational performance.